Uganda’s Nutrition and Early Child Development Project - Counting on Communication - Cabanero-Verzosa, Cecilia (World Bank, Washington, DC, 2012)
In 1998, a $34 million World Bank loan for the Nutrition and Early Child Development Project (NECDP) was approved to support the National Program of Action for Children. The NECDP covered about 8,000 communities in 20 of Uganda's 39 districts, selected based on levels of malnutrition, infant mortality, and primary school enrollment rates. The project sought to halve malnutrition among preschool children, raise primary school enrollment, reduce dropout and repetition rates, improve psycho-social and cognitive development, and increase the number of mothers practicing appropriate childcare.